Educational Policy: Understanding Tri Pusat Pendidikan (Education Centers) as Efforts to Reach Educational Objectives - Musbaing Musbaing (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2020)
This paper seeks to offer an interpretation of the significance of the core of education in an attempt to achieve public policy goals. Some publications addressing approaches, techniques, and models of learning as a means of understanding the ideal education, but there are still deficiencies attributable to educators or adults who do not see the environment as a place of training. The paper aims to provide parents, teachers, and the community with knowledge so that education is a joint obligation so that cooperation in the education system is complete.